2016
DOI: 10.1186/s12941-016-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-world daptomycin use across wide geographical regions: results from a pooled analysis of CORE and EU-CORE

Abstract: BackgroundPooled data from two large registries, Cubicin® Outcomes Registry and Experience (CORE; USA) and European Cubicin® Outcomes Registry and Experience (EU-CORE; Europe, Latin America, and Asia), were analyzed to determine the characteristics and clinical outcomes of daptomycin therapy in patients with Gram-positive infections across wide geographical regions.MethodsPatients receiving at least one dose of daptomycin between 2004 and 2012 for the treatment of Gram-positive infections were included. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…In a pooled analysis of the two large real-world registries, CORE in the USA and EU-CORE in Europe, daptomycin usage was analysed in 11 557 patients, of whom 8.6% were treated for osteomyelitis, with or without material, with an estimated clinical success rate of 77.7%. The promising role of daptomycin in such infections has been strengthened by the ability to use higher dosages of this molecule, up to 12 mg/kg, but also by in vitro studies showing its ability to penetrate bone tissue (Malizos et al, 2016;Seaton et al, 2016;Senneville et al, 2016). Traunmüller et al provided the first in vitro data regarding daptomycin bone penetration in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In a pooled analysis of the two large real-world registries, CORE in the USA and EU-CORE in Europe, daptomycin usage was analysed in 11 557 patients, of whom 8.6% were treated for osteomyelitis, with or without material, with an estimated clinical success rate of 77.7%. The promising role of daptomycin in such infections has been strengthened by the ability to use higher dosages of this molecule, up to 12 mg/kg, but also by in vitro studies showing its ability to penetrate bone tissue (Malizos et al, 2016;Seaton et al, 2016;Senneville et al, 2016). Traunmüller et al provided the first in vitro data regarding daptomycin bone penetration in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Two patients in our cohort developed eosinophilic pneumonitis, an unusual and poorlyunderstood complication associated with daptomycin. The largest study to date of complications secondary to daptomycin administration found, in 11,557 patients, an estimated incidence of eosinophilic pneumonitis of 0.03% 24 . A review of the US FDA Adverse Event Reporting System database identified 7 definite, 13 probable, and 38 possible cases of daptomycin-induced eosinophilic pneumonia 25 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that daptomycin has an adverse effect concerning creatinine phosphokinase (CPK) elevation . To date, the safety of daptomycin treatment has been widely investigated in relation to various types of infections and pathogens . Although a few reports describe the higher risk of CPK elevation in high‐dose treatment, almost all other previous reports demonstrated the safety of daptomycin treatment with a low or no significant incidence of CPK elevation or other adverse effects, even with high‐dose treatment .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…5 To date, the safety of daptomycin treatment has been widely investigated in relation to various types of infections and pathogens. [6][7][8][9][10][11][12][13][14][15] Although a few reports describe the higher risk of CPK elevation in high-dose treatment, 12 almost all other previous reports demonstrated the safety of daptomycin treatment with a low or no significant incidence of CPK elevation or other adverse effects, even with high-dose treatment. 7,8,10,[12][13][14][15] Previously, C trough levels of 24.3 μg/mL were reported as a breakpoint of CPK elevation.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%